2018
DOI: 10.1002/ppap.201800150
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of a non‐thermally operated electrosurgical argon plasma source by electron spin resonance spectroscopy

Abstract: Non‐thermal plasma treatment is one of the promising options for local anti‐neoplastic treatment of dysplastic lesions and early intraepithelial cancer. Primarily, the antiproliferative properties are driven through the generation of reactive oxygen and nitrogen species. In this study, we investigated the amount and distribution of reactive species generated by a non‐thermally operated electrosurgical argon plasma source using electron spin resonance (ESR) spectroscopy. During the plasma treatment of both, aqu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
24
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 20 publications
(26 citation statements)
references
References 32 publications
2
24
0
Order By: Relevance
“…Human mucosa is the main target tissue for future plasma-based treatment procedures of many chronic inflammatory, precancerous and cancerous diseases [33]. In previous work, we characterized the principal ability of electrosurgical argon plasma sources to perform non-thermal plasma treatment of human tissue, referred to as NIPP [11]. In this study, we demonstrated that dynamic tissue treatment by a next generation electrosurgical plasma source (VIO ® 3, APC 3) was not associated with potentially tissue harming surface temperatures (Figure 4).…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Human mucosa is the main target tissue for future plasma-based treatment procedures of many chronic inflammatory, precancerous and cancerous diseases [33]. In previous work, we characterized the principal ability of electrosurgical argon plasma sources to perform non-thermal plasma treatment of human tissue, referred to as NIPP [11]. In this study, we demonstrated that dynamic tissue treatment by a next generation electrosurgical plasma source (VIO ® 3, APC 3) was not associated with potentially tissue harming surface temperatures (Figure 4).…”
Section: Discussionmentioning
confidence: 99%
“…Thus, the investment and operation costs for these devices are relatively high. Similar to conventional CAP devices, the plasma effluent of non-thermally operated electrosurgical argon plasma sources contains diverse biologically reactive factors (charged particles and molecules, free radicals, ultraviolet, and infrared radiation) [11]. Commonly used electrosurgical argon plasma sources are devices for high-frequency (HF)-based surgery.…”
mentioning
confidence: 99%
See 3 more Smart Citations